A Series of Past-Life Visions and Intuitive Impressions Surfacing in Middle Adulthood with Behavioral Influences Beginning in Childhood - Matlock, James G. (Journal of Scientific Exploration, 2024)
In the wake of several traumatic experiences, a French woman in her early 50s began to have visions and intuitive impressions about seven past lives she felt she had lived. She was able to verify memories of the most recent life and identify the deceased, an American Marine fatally wounded in Vietnam. It then became clear that she had been subliminally influenced by this life in various ways from childhood, most strongly following an NDE at 18. On the eve of the Russian invasion of Ukraine, she began to have detailed visions of a Don Cossack who had served in the Imperial Guard of Catherine the Great and Alexander I, dying during Napoleon’s retreat from Moscow in 1812. Although the Cossack story is plausible, it has not been possible to investigate it or to identify the individual involved; nonetheless, here too there are apparent behavioral influences on the subject’s present life. Although the subject recalled the other five lives in fragments only, some of these also seem to have impacted her unconsciously. This study explores the nature of past-life remembering and demonstrates how presumptive past lives may exercise an influence behaviorally, emotionally, and somatically, even in the absence of conscious recall.